2021
DOI: 10.1177/17534259211036186
|View full text |Cite
|
Sign up to set email alerts
|

The TNF-α (–238 G/A) polymorphism could protect against development of severe sepsis

Abstract: Primary responses in sepsis-mediated inflammation are regulated by pro-inflammatory cytokines. Variations in the cytokine genes might modify their transcription or expression, plasma cytokines levels and response to sepsis. Activation protein-1 (AP-1) and NF-κB regulate cytokines gene expression in sepsis. A total of 90 severely septic and 91 non-infected patients were prospectively studied. IL-1α ( –889 C/T), IL-1β ( +3954 C/T), IL-6 ( –174 G/C), TNF-α ( –238 G/A), TNF-α ( –308G/A), IL-8 ( –251A/T) and IL-10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…17,18 Moreover, TNFα gene polymorphism could protect against the development of severe sepsis in humans. 19 On the other hand, IL1α, but not IL1β was shown to drive IL1R1-dependent sepsis lethality in neonatal mice. 20 Based on these data, further animal studies assessing the efficiency of TXA protection against sepsis should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 Moreover, TNFα gene polymorphism could protect against the development of severe sepsis in humans. 19 On the other hand, IL1α, but not IL1β was shown to drive IL1R1-dependent sepsis lethality in neonatal mice. 20 Based on these data, further animal studies assessing the efficiency of TXA protection against sepsis should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The LPS stimulation of TNF α expression in the liver is known to induce hepatocyte apoptosis, liver failure, and even lethal effect 17,18 . Moreover, TNF α gene polymorphism could protect against the development of severe sepsis in humans 19 . On the other hand, IL1 α , but not IL1 β was shown to drive IL1R1‐dependent sepsis lethality in neonatal mice 20 .…”
Section: Discussionmentioning
confidence: 99%
“…IL-6/LY# ratio act like a microcosm of the immune system. There are still many inflammatory factor and cytokines may provide us with more information during the occurrence and development of sepsis, such as IL-8, IL-10, and TNF-α (29)(30)(31). Studies contains varies cytokines and inflammatory biomarkers should be carried out to explore interactions between the hyperinflammatory state and subtypes of T-cell transition in patients with sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…This paper observed that GA reduced the degrees of TNF- α , IL- β , and HMGB1 by ELISA. The levels of TNF- α and MCP-1 in plasma of 90 patients with severe sepsis were higher than those in the controls [ 28 ]. It was pointed out that improving inflammation can treat lung function and tissue injury.…”
Section: Discussionmentioning
confidence: 99%